A nightmare on Elm Street [videorecording (Blu-Ray)] - Craven, Wes; Saxon, John, 1935-2020; Blakley, Ronee; Langenkamp, Heather, 1964-; Depp, Johnny (New Line Home Entertainment, 2010)
Freddy homicidally haunts the sleep of Elm Street teens. Nancy is one of those teens having nightmares about the frightening, badly-scarred figure who wears a glove with razor-sharp 'finger knives.' She quickly discovers that her friends are having similar dreams. When the teens begin to die, Nancy realizes that she will have to stay awake in order to survive. Uncovering Freddy's secret identity and his connection to the teens, Nancy, plots to draw him out into the real world.